Agricultural terraces in the Mediterranean: medieval intensification revealed by OSL profiling and dating. (June 2021) - Turner, Sam; Kinnaird, Tim; Varinlioğlu, Günder; Şerifoğlu, Tevfik Emre; Koparal, Elif; Demirciler, Volkan; Athanasoulis, Dimitris; Ødegård, Knut; Crow, Jim; Jackson, Mark; Bolòs, Jordi; Sánchez-Pardo, José Carlos; et al.
Abstract : Abstract: The history of agricultural terraces remains poorly understood due to problems in dating their construction and use. This has hampered broader research on their significance, limiting knowledge of past agricultural practices and the long-term investment choices of rural communities. The authors apply OSL profiling and dating to the sediments associated with agricultural terraces across the Mediterranean region to date their construction and use. Results from five widely dispersed case studies reveal that although many terraces were used in the first millennium AD, the most intensive episodes of terrace-building occurred during the later Middle Ages ( c . AD 1100–1600). This innovative approach provides the first large-scale evidence for both the longevity and medieval intensification of Mediterranean terraces.